Pulmonary capillary hemangiomatosis: an unusual cause of primary pulmonary hypertension in pediatric age group - Thapar, Vayom; Sarthalia, Madhur; Kumar, G. Durga Phani; Saini, Susheel K.; Kumari, Seema; Saini, Ajay K. (International Journal of Contemporary Pediatrics, 2023)
Pulmonary capillary hemangiomatosis (PCH) is a rare and controversial entity that is known to be a cause of pulmonary hypertension and is microscopically characterized by proliferation of dilated capillary-sized channels along and in the alveolar walls. Clinically, it is mostly seen in adults. PCH’s main clinical presentations are progressive dyspnea, fatigue, hemoptysis, palpitations and later irreversible pulmonary hypertension and right-sided heart failure. It is characterized by severe hypoxemia, centrilobular ground-glass opacities on computed tomography and pulmonary congestion triggered by pulmonary vasodilating therapy. The imaging features include diffuse centrilobular ground‑glass opacities with features of pulmonary hypertension. We present a case of PCH in a 4‑year‑old boy who was diagnosed with post-partum hemorrhage (PPH) in echocardiography and computed tomography of the thorax.